232k views
5 votes
How do you solve this systems of equations problem

2r +3s=-5
6s=2r

1 Answer

1 vote

Answer:

see explanation

Explanation:

Given the 2 equations

2r + 3s = - 5 → (1)

6s = 2r → (2) ( divide both sides by 2 ), then

r = 3s

Substitute r = 3s into (1)

2(3s) + 3s = - 5

6s + 3s = - 5

9s = - 5 ( divide both sides by 9 )

s = -
(5)/(9)

Substitute this value into either of the 2 equations and evaluate for r

Substituting into r = 3s, then

r = 3 × -
(5)/(9) = -
(5)/(3)

Solution is r = -
(5)/(3) and s = -
(5)/(9)

User Jonna
by
5.1k points